2020
DOI: 10.31018/jans.vi.2293
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and management of two cichlid species in the Shatt Al-Arab River, Iraq

Abstract: Cichlids are invasive fish to Iraqi waters and became well established and prevailing in different waters. Despite that, there is no stock assessment study conducted for these fish. So, growth, mortality, recruitment and yield-per-recruit of two cichlid’s species; Coptodon zillii and Oreochromis aureus from the Shatt Al-Arab River, Iraq were evaluated from November 2015 to October 2016 using the FiSAT software. A total of 1285 C. zillii (2.9-24.0 cm TL) and 1353 O. aureus (4.5-25.0 cm TL) were examined. Length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…However, some authors used scales for determining age and growth, and also reported mortality and yield-per-recruit of O. aureus such as [16] in Rosetta branch of the Nile River, Egypt and [17] in Nozha Hydrodrome, Egypt. Recently, the population dynamics and management of O. aureus in Shatt Al-Arab River, Iraq has been reported by Mohamed and Abood [18], and the present study is a continuation of investigation on this species in Iraq.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…However, some authors used scales for determining age and growth, and also reported mortality and yield-per-recruit of O. aureus such as [16] in Rosetta branch of the Nile River, Egypt and [17] in Nozha Hydrodrome, Egypt. Recently, the population dynamics and management of O. aureus in Shatt Al-Arab River, Iraq has been reported by Mohamed and Abood [18], and the present study is a continuation of investigation on this species in Iraq.…”
Section: Introductionmentioning
confidence: 52%
“…The growth parameters obtained in this study eported from different geographic locations which were obtained by applying FiSAT II software and scales analysis are presented in ∞) in this study was higher than those recorded for this species Rosetta branch, Shatt Al-Arab River, Iraq [18], whereas these were lower than those found in Aguamilpa Reservoir, Mexico Nozha Hydrodrome, Egypt [17]. The value of K was within the range observed in other populations of O. aureus, where the lowest value (0.21) was documented by Mahmoud et al [17] from the Nozha Hydrodrome, Egypt, highest one was 0.56 reported by Mehanna [13] from the El-Raiyan Lakes, Egypt.…”
Section: Yield Per Recruit (Y'/r) and Biomassmentioning
confidence: 61%
See 1 more Smart Citation
“…Also, El-Kasheif et al [11] noted that the values of Epresent, E0.1 and Emax were 0.43, 0.51 and 0.64, respectively for the species in El-Bahr El-Faraouny Canal, Egypt. Mohamed and Abood [31] reported that the exploitation rates for C. zillii and O. aureus in the Shatt Al-Arab river were below the biological target reference points (F0.1 and Fmax), indicated that these species were also not overexploited.…”
Section: Length Range (Cm) (B) Regionmentioning
confidence: 99%
“…Consequently, it became necessary to compiled information about the population status of these invaded cichlids in Iraqi waters. Recently, the population dynamics and management of two cichlid species (C. zillii and O. aureus) in Shatt Al-Arab River have been studied by Mohamed and Abood (2020) [31], and the present study is a continuation of investigation on tilapia fish in Iraq.…”
mentioning
confidence: 94%